The growth patterns, condition factors, and feeding habits of trichogaster sp. in Rawa Blorep Merauke Regency - Rumbara, Mei Elsa; Sunarni, Sunarni; Merly, Sendy L (Universitas Musamus, Merauke, Papua, 2024)
Blorep Swamp is a swamp in the urban area of ​​Merauke Regency, located close to residential areas, and is known as a catchment area. This research aims to determine the growth patterns, condition factors, and eating habits of Trichogaster sp. This research lasted three months using a purposive sampling method from April to June 2023. This research found that 123 samples of Trichogaster sp. were obtained, with 113 pieces of fish stomachs containing food and ten empty. Furthermore, every month, the growth pattern of Trichogaster sp. shows a different way. In April, the growth pattern is Positive Allometric (3,13216); meanwhile, in May and June, the growth pattern is Negative Allometric value approximately 2,73986 – 2,33476). The average condition factor value during the research in April ranged from 0.5790 – 0.8767; in May, the average value was 0.5380 – 1.4482, and in June, the average value was 0.6932 – 1.4896. The Stomach content of the fish found that there are seven species of phytoplankton from four classes: the first class, Bacillariophyceae with species Chlorella sp., Climacosphenia monolinear, Navicula sp., the second class of Diatoms with species Diploneis fusca, third class Xanthophyceae with species Surirella sp., and a fourth class with species Chlorophyceae, Tribonema sp. nd Ulothrix sp. The highest species obtained is Chlorella sp., with a total of 4.871, and the lowest species is Surirella sp., with 199 received from samples obtained during research in the Blorep swamp.